2020
DOI: 10.1177/0020852320921220
|View full text |Cite
|
Sign up to set email alerts
|

The influence of team members’ motivation and leaders’ behaviour on scientific knowledge sharing in universities

Abstract: This article aims to analyse the influence of team members’ motivation and leaders’ behaviour on knowledge sharing among the academics of a research project team. To that end, a study of 678 academic researchers belonging to project teams linked to several Spanish universities was conducted. Hierarchical regression analysis was used to analyse the data, and the results reveal that leaders with a knowledge-oriented style have a positive influence on the knowledge shared among the members of their research team.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 53 publications
1
32
0
1
Order By: Relevance
“…Fifth, we would like to acknowledge that there may be other variables such as team leadership or corporate culture that may very well impact on the employees' attitudes highlighted in our study. Concretely, team leadership has been widely accepted as a process with the capability of influencing employees' attitudes and behaviors such as their motivation [99]. In fact, we propose future studies to analyze the relationships found here, testing the moderating effects based on the differential impacts that various leadership styles are able to exert on employees' attitudinal, behavioral, and cognitive outcomes [100].…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Fifth, we would like to acknowledge that there may be other variables such as team leadership or corporate culture that may very well impact on the employees' attitudes highlighted in our study. Concretely, team leadership has been widely accepted as a process with the capability of influencing employees' attitudes and behaviors such as their motivation [99]. In fact, we propose future studies to analyze the relationships found here, testing the moderating effects based on the differential impacts that various leadership styles are able to exert on employees' attitudinal, behavioral, and cognitive outcomes [100].…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Despite the great progress made by scholars to understand motivational factors to team KS , some issues hinder further investigations. First, though prior research conclude that motivation plays a crucial role in predicting KS, the findings have been inconclusive (Ballesteros-Rodríguez et al, 2020; and managerially impractical (Foss et al, 2010). KS motivations have mostly been divided into extrinsic and intrinsic motivations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, formal evaluations, performance measures, and comparative indicators are introduced to assess academics’ capacity to get research results. Therefore, academics are forced to compete to achieve promotions, publications, and funds for projects ( Ballesteros-Rodríguez et al, 2020 ; Dusdal and Powell, 2021 ). Under such circumstances, the collaboration between and among researchers is increasingly emphasized at both the national and international levels.…”
Section: Literature Reviewmentioning
confidence: 99%